USING INTERACTIVE TECHNIQUES IN NATIVE LANGUAGE AND READING LITERACY CLASSES (Academia Science Repository, 2023)
Currently, there is a broad emphasis on educational issues in schools. Therefore, each elementary school teacher should educate students through interactive methods to educate moral characteristics in them. We will talk about several methods in this article.